Oral health knowledge, attitudes, behaviours and status among international post-secondary students: a scoping review - Yassin, Hassan W.; Fida, Shahzaib; Alphonsus, Khrisha; Lieffers, Jessica; Singh, Amrinderbir (Frontiers in Oral Health, 2025)
ObjectiveThis scoping review aims to review and synthesize existing literature on oral health knowledge, attitudes, behaviours, barriers, and status among international post-secondary students.MethodsUsing the Arksey and O'Malley framework, MEDLINE, Embase, Dentistry & Oral Sciences Source, CINAHL, Web of Science, and Scopus databases were searched in June 2024 for selected oral health and international student keywords. Manual searches of reference lists and citations were also conducted. Original research studies in English language were included, with no geographical or date limitations. Using Rayyan, duplicates were removed, and then two authors independently screened available literature according to eligibility criteria; inconsistencies or disagreements were resolved through a third author.ResultsThe search yielded 984 articles. After removal of duplicates and those inconsistent with our inclusion criteria, 14 articles remained. In total, 13/14 articles used a cross-sectional design implementing surveys or interviews; only 4 articles presented objective clinical measures (e.g., DMFT, objective periodontal measures). Some included articles provided information about dietary habits relevant to oral health; however, information captured was limited. Overall, compared to the domestic students, international students were reported to have poorer oral health status; more gaps in their knowledge, attitudes and behaviours regarding oral health; and were also less likely to obtain routine oral health care.ConclusionInternational students may face significant challenges in managing and optimizing their oral health vs. domestic students due to various factors (e.g., acculturation stress, finances, diet, academic stress etc.). Post-secondary institutions may want to consider focusing on supporting and empowering international students to access oral health care on a regular basis through targeted interventions. To design impactful interventions, future community engaged research is needed to better understand the perspectives of international students regarding their oral health status, knowledge, attitudes, behaviours, needs, and aspirations.